Preliminary characterization of a spray-dried hydrocolloid from a high andean algae (nostoc sphaericum) - Choque Quispe, David (2022)
The search for new natural sources of hydrocolloids with stabilizing, thickening, and good binding capacity, from raw materials that are environmentally friendly and that contribute to the circular economy is a challenge for the food industry. The aim of the study was the preliminary characterization of a spray-dried hydrocolloid from high Andean algae Nostoc sphaericum. Four ecotypes of algae from Peruvian high Andean lagoons located above 4000 m were considered. The samples were collected in the period March–April 2021 and were subjected to a spray drying process in an aqueous medium. The characterization showed that the dehydrated nostoc ecotypes presented high protein and carbohydrate content, making it a potential material for direct use as a functional food for humans. The spray-dried product presented good stability for its use as a hydrocolloid, with zeta potential values ( ), around 30 mV, evidencing the presence of -CO-, -OH, -COO-, and -CH groups, characteristic of polysaccharides, representing 40% of total organic carbon on average, giving it low water activity values and particle size at the nanometric level. Major minerals such as Ca (>277 mg/100 g), Mg (>19.7 mg/100 g), and Fe (>7.7 mg/100 g) were reported. Spray-dried nostoc is a hydrocolloid material with high potential for the food industry, with good nutritional content and techno-functional behavior.